Cytotoxic Epipolythiodioxopiperazine Alkaloids from Filamentous Fungi of the Bionectriaceae - Figueroa, Mario (2012)
Bioactivity-directed fractionation of the organic extracts of two filamentous fungi of the Bionectriaceae, strains MSX 64546 and MSX 59553 from the Mycosynthetix library, led to the isolation of a new dimeric epipolythiodioxopiperazine alkaloid, verticillin H (1), along with six related analogues, Sch 52900 (2), verticillin A (3), gliocladicillin C (4), Sch 52901 (5), 11′-deoxyverticillin A (6), and gliocladicillin A (7). The structures of compounds 1–7 were determined by extensive NMR and HRMS analyses, as well as by comparisons to the literature. All compounds (1–7) were evaluated for cytotoxicity against a panel of human cancer cell lines, displaying IC(50) values ranging from 1.2 µM to 10 nM. Compounds 1–5 were examined for activity in the NF-κB assay, where compounds 2 and 3 revealed activity in the sub-micromolar range. Additionally, compounds 1, 3, and 4 were tested for EGFR inhibition using an enzymatic assay, while compound 3 was examined against an overexpressing EGFR(+ve) cancer cell line.